Discontent With What? Linking Self-Centered and Society-Centered Discontent to Populist Party Support - Heiko Giebler; Magdalena Hirsch; Benjamin Schürmann; Susanne Veit (Political Studies, 2021)
Previous studies aimed at explaining populist support emphasize the crucial role of populist attitudes and ideology among the general population. With respect to the role of discontent and grievances as drivers of populist support - often at the heart of theoretical work on populism - however, empirical results are rather mixed. We argue that the apparent contradictions are partly due to insufficient conceptualization of discontent. We distinguish between societal-centered discontent, which is more based on a general, negative subjective assessment of society, and self-centered discontent that expresses a negative assessment of one's personal situation. In line with our expectations, regression results for Germany confirm that society-centered discontent, but not self-centered discontent, is important for populist party support. Moreover, we find that society-centered discontent also moderates the relation between populist attitudes and populist support. We conclude that beyond ideologies, populism capitalizes on the cultivation of collective - but not individual - discontent.
Keywords: 300; society-centered discontent; populist attitudes; Alternative for Germany; populist party support; self-centered discontent